Peningkatan Keaktifan Belajar Siswa dengan Menggunakan Model Small Group Discussion Siswa Sekolah Dasar - Nurhalisa, Siti; Mufarizuddin, Mufarizuddin; Sumianto, Sumianto; Fadhilaturrahmi, Fadhilaturrahmi; Marta, Rusdial (MODELING: Jurnal Program Studi PGMI, 2023)
This research is motivated by the low learning activity of fifth grade students at UPT SDN 005 Bukit Ranah. One of the solution to solve this problem is to use the small group discussion model. This study aims to improve the learning activity of fifth grade students at UPT SDN 005 Bukit Ranah with 34 students, with a of 18 male students ang 17 female students. The research method was classroom action research (PTK) implemented in two learning cycle consists of two meetings and four learning stages, namely: planning, implementing, observing, and reflecting. The time of the research was carried out in May 2023. Data collection technique using qualitative analysis and quantitative analysis. Based on the result of the learning activity of the fifth grade students at UPT SDN 005 Bukit Ranah in the pre-ativity with a learning mastery percentage of 41,17%. In the first n cycle I meeting I with a percentage of study completion of 44,11%, students who completed only 15 students and cycle I of meeting II increased with a percentage of learning completion of 52,94%, students who completed only 18 students. In cycle II meeting I also increased with a percentage of learning completion of 85,29%, students who completed only 29 students and cycle II of meeting II experienced another increase with a percentage of study completion of 91.17%, students who completed 31 students. So it can be concluded that by using the small group discussion model it can improve learning activity of fitft grade students at UPT SDN 005 Bukit Ranah. Keywords: Stedents Learning Activity, Small Group Discussion, Classroom Action Research.